Perancangan meja TV dengan desain parametrik menggunakan bahan limbah kayu lapis - Fariz, Nuthqy; Hutasoit, Nicolas MP; Sany, Nukhbah (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2024)
The Indonesian wood industry is an industry that is favorable by the foreign consumers, with a steady increase in sales—even in the midst of a pandemic. One of the impacts arising from the increased production process is the increased wood waste produced. This research was conducted as an effort to utilize the abundant wood waste to become a TV table furniture that has high aesthetic value by using a parametric design. The method used is the design thinking, with the research results in the form of a working drawing design and a prototype of TV table furniture with a parametric design. The aesthetic assessment showed that 77% of the total respondents stated that the design and prototype of the TV table had an aesthetic shape and value.